2019
DOI: 10.1088/1755-1315/294/1/012035
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of retrofitting tools for residential buildings

Abstract: Retrofitting of existing buildings offers significant opportunities to reduce global energy use and greenhouse gas emissions. Therefore, it is considered as one of the main approaches to achieve sustainability in the built environment at a relatively low cost. Although there is a wide range of retrofitting technologies available, methods to identify the most cost-effective measures for each project remain a major technical challenge. Numerous projects have been developed worldwide to face this challenge with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In the study by Gonzalez-Caceres et al (2019), an extensive review of eighteen tools used for property renovation and retrofit for civil construction was carried out, grouped into three categories: renovation assessment, financial assessment and knowledge transfer. From this review, it can be concluded that development and innovation in retrofitting tools benefit a wide range of stakeholders, including researchers, organizations and even countries.…”
Section: Governance and Innovation In Civil Constructionmentioning
confidence: 99%
“…In the study by Gonzalez-Caceres et al (2019), an extensive review of eighteen tools used for property renovation and retrofit for civil construction was carried out, grouped into three categories: renovation assessment, financial assessment and knowledge transfer. From this review, it can be concluded that development and innovation in retrofitting tools benefit a wide range of stakeholders, including researchers, organizations and even countries.…”
Section: Governance and Innovation In Civil Constructionmentioning
confidence: 99%
“…The refurbishment laws and regulations might vary depending on the country, but the need for Energies 2023, 16, 3930 2 of 24 an energy assessment is constant. Therefore, a key point of the retrofit plan is choosing the most suitable mathematical model for an accurate energy assessment of the existing and refurbished building state [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [15] reviewed eighteen retrofit tools and classified them into three categories: retrofit assessment, financial assessment, and knowledge transfer. These tools aim to infer the best energy retrofit options based on input data.…”
Section: Introductionmentioning
confidence: 99%